2009
DOI: 10.1080/00076790903266844
|View full text |Cite
|
Sign up to set email alerts
|

Risk and risk management in the Liverpool slave trade

Abstract: The profits of the Liverpool slave trade are infamous, if somewhat more realistically represented in recent literature. Contemporaries and historians have posited that these higher profits were required to entice merchants into the trade because of the higher risks. However, there is very little work which investigates whether the risks of the slave trade really were higher than other similar opportunities. This article uses the case study of Liverpool slave traders to investigate the risks within the slave tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 29 publications
0
19
0
1
Order By: Relevance
“…La decisión dependía en cierta medida del mercado de destino. Por ejemplo, para los barcos destinados hacia los mercados africanos, los cuales eran percibidos como ampliamente impredecibles, negociantes americanos y británicos entregaban a los capitanes de barco órdenes que dejaban un gran margen de actuación y de toma de decisiones a estos (Haggertty, 2009). Otra opción era recurrir a un agente conocido como sobrecargo, quien no era otro que un representante encargado ya fuese de seleccionar el consignatario, ya de ejecutar él mismo las órdenes recibidas o de actuar de la manera más conveniente según su interpretación de las variables del mercado donde llegaba.…”
Section: Seleccionar Los Agentes (Oportunistamente)unclassified
“…La decisión dependía en cierta medida del mercado de destino. Por ejemplo, para los barcos destinados hacia los mercados africanos, los cuales eran percibidos como ampliamente impredecibles, negociantes americanos y británicos entregaban a los capitanes de barco órdenes que dejaban un gran margen de actuación y de toma de decisiones a estos (Haggertty, 2009). Otra opción era recurrir a un agente conocido como sobrecargo, quien no era otro que un representante encargado ya fuese de seleccionar el consignatario, ya de ejecutar él mismo las órdenes recibidas o de actuar de la manera más conveniente según su interpretación de las variables del mercado donde llegaba.…”
Section: Seleccionar Los Agentes (Oportunistamente)unclassified
“…If a set of bills were issued at three, six and nine months' sight, the terms of credit would hence be six months. 13 Each tranche of bills could be held until maturity, at which point their full value could be redeemed, or immediately discounted for cash at a rate of (Haggerty 2009;Inikori 2002). 14 A comprehensive study of one Liverpool merchant's papers found that slave traders disliked discounting bills drawn for American sales, even when they extended to several years length (Anderson 1977).…”
Section: Geography Of Slavery In the British Americas 1755-1807mentioning
confidence: 99%
“…Where observations of credits could not be made, they assumed a linear progression in terms from nine months in 1756-1775, to twelve months in 1776-1793, and fifteen months in 1794-1807. More recently, Pearson and Richardson (2008) found that credits ranged from six months in the mid-eighteenth century, to eighteen months at the end of the century, and Haggerty (2009) determined that bills extended from twelve months in 1770, to twenty-four months by 1787.…”
Section: Geography Of Slavery In the British Americas 1755-1807mentioning
confidence: 99%
“…Slavery and the slave trade remains a strong theme in the periodical literature in the wake of the bicentenary of abolition. Haggerty explores the risks of the trade through a case study of Liverpool merchants. While riskier than other Atlantic trades, it is clear that individuals understood those risks and had sound techniques for their management.…”
Section: (Iv) 1700–1850
Anne L Murphy
University Of Hertfordshirementioning
confidence: 99%